Penser le(s) patrimoin(e)s gastronomique(s) : à propos de quelques obstacles à l’appréhension d’un protéiforme au cœur d’un incertain - Julia Csergo (In Situ)
The aim of this article is to situate the gastronomic heritage in the broader history of the narrative representation of heritage in France. More specifically, it aims at analysing the main obstacles that stood in the way of how this heritage could be taken into account and how thinking about it evolved. We identify three main obstacles, which we propose to set forth as keys to understanding the confusion—rather than ignorance—that this heritage has suffered from. The first obstacle relates to the conditions in which this new heritage emerged, at a time of effervescence and uncertainty around the very notion of heritage, when anything and everything could be seen as heritage. The second obstacle is in the diversity of headings under which the gastronomic heritage has been aligned, between culture and agriculture, between apparent institutionalisation and social designation. The third obstacle, underlying the first two perhaps, is associated with the way it belongs to two separate heritage traditions that only achieved some form of synthesis when the intangible cultural heritage was properly recognised.